Analisis Produktivitas dan Kualitas Buah Stoberi var Sujarli (Rosalinda) Berdasarkan Model Budidaya dan Pengolahan Citra Digital - Sri Handayani Nofiyanti; Yohanes Setiyo; Mukhes Sri Muna; I Putu Surya Wirawan; Nur Ida Winni Yosika (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Strawberry (Fragaria sp.) is a high-value horticultural commodity with broad market potential, particularly in tropical highland areas such as Bedugul, Bali. However, its productivity and fruit quality are often constrained by climatic fluctuations and limited application of appropriate cultivation technologies. This study aimed to evaluate the productivity and fruit quality of Sujarli (Rosalinda) strawberry variety under four cultivation models: conventional open field, tunnel, fertigated open field, and greenhouse. In addition, a predictive model for Total Soluble Solids (TSS) content was developed using fruit color parameters obtained through digital image analysis. A total of 100 strawberry samples across five ripening stages were analyzed for biometrical characteristics (length, diameter, and weight), pH, and TSS. Image analysis was performed in two color spaces, namely RGB and HSV, and the corresponding color values were used as input variables in a multiple linear regression (MLR) model to predict TSS values. The results showed that the fertigated open field system produced strawberries with good physical and chemical quality, making it a feasible option for small-scale farmers. The MLR model based on HSV color space outperformed the RGB-based model, achieving R² values of 0.826 (training) and 0.775 (testing), with lower RMSE values as well. These findings support the use of digital color data as a non-destructive indicator for assessing the quality of strawberries during postharvest evaluation.